2013
DOI: 10.1186/1746-1596-8-107
|View full text |Cite
|
Sign up to set email alerts
|

Primary renal teratoma: a rare entity

Abstract: Teratomas are neoplasms that arise from pluripotent cells and can differentiate along one or more embryonic germ lines. Renal teratoma is an exceedingly rare condition. Teratomas commonly arise in the gonads, sacrococcygeal region, pineal gland, and retroperitoneum. They present mainly as an abdominal mass with few other symptoms. Majority of the tumors are benign, situated on the left side and para renal, occasional lesions are bilateral. If diagnosed early, they are amenable to curative excision.Renal terato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…The differentiation between these two neoplasms in the kidney is often problematic. Although teratomas and teratoid WT may have similar histology, teratomas display unequivocal organogenesis such as stratified squamous epithelium associated with skin adnexa, intestinal mucosal epithelium surrounded by smooth muscle bundles, and neuroglial tissue associated with choroid plexus epithelium (34). In occasional cases of TWT, the serum AFP levels may be elevated.…”
Section: Casementioning
confidence: 99%
“…The differentiation between these two neoplasms in the kidney is often problematic. Although teratomas and teratoid WT may have similar histology, teratomas display unequivocal organogenesis such as stratified squamous epithelium associated with skin adnexa, intestinal mucosal epithelium surrounded by smooth muscle bundles, and neuroglial tissue associated with choroid plexus epithelium (34). In occasional cases of TWT, the serum AFP levels may be elevated.…”
Section: Casementioning
confidence: 99%
“…Intrarenal teratomas are extremely rare [2 , 5] and only 20 case reports have been reported in the literature from 1934 to 2004. Out of these cases, only 5 had associated congenital abnormalities such as horseshoe kidney, prune belly syndrome, and duplicated collecting system [6] .…”
Section: Discussionmentioning
confidence: 99%
“…The latest renal teratoma was described by Balanji et al in 2018 where they found a mature teratoma within the renal pelvis [7] . The most common location for teratomas are as follows: 40% in sacrococcygeal region, 25% in ovary, 18% in mediastinum and neck, 12% in testis, and 5% in brain tissues [5 , 8] . Its occurrence is considered less than 5% in the abdomen [5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case tumor was not arising in kidney it originated in retroperitoneum and due to extremely large size it displaced left kidney and its hilum to right side casing it appears like 'acquired crossed nonfused renal ectopia'. 10 Various renal migration anamolies are congenital such as simple renal ectopia -abnormal position of the kidney in the cranial or caudal direction on same side of origin. There are 4 different recognized types of simple renal ectopia:…”
Section: Discussionmentioning
confidence: 99%